Economic Growth and Poverty Reduction in Sub-Saharan Africa 2015
DOI: 10.1093/acprof:oso/9780198728450.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Informal Economy, Economic Growth, and Poverty in Sub-Saharan Africa

Abstract: The role that informality plays in the shaping of economies is not yet very well understood. In many economies anxious to modernize and grow faster, informality is seen as a challenge that has to be tackled to move them to new levels of development. But there is little evidence that trying to induce change directly in informal economic entities benefits the larger economy in any significant way. Indeed, while the institutional economics literature provides good frameworks for understanding both the economic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
1
29
0
1
Order By: Relevance
“…Unemployment, low productivity in agriculture and the need to migrate to the urban to search for employment has forced millions of the youth in developing countries to engage in informal trade (Aryeetey, 2009). Globally, it was estimated that in 2000s, the informal sector constituted 18% of economy in OECD countries, 38% of the economy in transition countries and 41% in developing countries.…”
Section: Background To the Studymentioning
confidence: 99%
“…Unemployment, low productivity in agriculture and the need to migrate to the urban to search for employment has forced millions of the youth in developing countries to engage in informal trade (Aryeetey, 2009). Globally, it was estimated that in 2000s, the informal sector constituted 18% of economy in OECD countries, 38% of the economy in transition countries and 41% in developing countries.…”
Section: Background To the Studymentioning
confidence: 99%
“…Okpara and Kabongo (2009) suggested that SMEs internal and external components differs significantly among developing countries. There are many studies that explored factors that hinders SMEs development (Arasti et al, 2012b;Aryeetey, 2015;Watson and Everett, 1996). Nonetheless, understanding the lack of SMEs growth requires understanding the common problems and differences in organizational and market relations (Arasti et al, 2012b;Aryeetey, 2015;Watson and Everett, 1996).…”
Section: Literature Review and Conceptual Designmentioning
confidence: 99%
“…There are many studies that explored factors that hinders SMEs development (Arasti et al, 2012b;Aryeetey, 2015;Watson and Everett, 1996). Nonetheless, understanding the lack of SMEs growth requires understanding the common problems and differences in organizational and market relations (Arasti et al, 2012b;Aryeetey, 2015;Watson and Everett, 1996). Thus, this creates opportunity to explore the determinants of SMEs growth in Sub-Sahara Africa as country components differ on many scales including social and cultural.…”
Section: Literature Review and Conceptual Designmentioning
confidence: 99%
“…Furthermore, activities of this sector are not captured in official records and usually they have no formal income remunerations. Similarly, Edward (2008) maintains that the informal sector is nothing more than heterogeneous enterprises outside any contractual arrangement or as pointed by Aryeetey (2009) enterprises without neither official status nor any social security by the government and involved in smuggling. In short, Nduru (2004) concludes that the informal trade takes different forms and is known under different names (unrecorded trade; illegal trade; unofficial trade; trade subject to over and under invoicing, smuggling, hoarding).…”
Section: Review Of Literaturementioning
confidence: 99%